Facile and rapid detection of respiratory syncytial virus using metallic nanoparticles - Valdez, Jesús; Bawage, Swapnil; Gomez, Idalia; Singh, Shree Ram (Springer Nature, 2016)
Background: Respiratory syncytial virus (RSV) causes severe respiratory infection in infants, children and elderly. Currently, there is no effective vaccine or RSV specific drug for the treatment. However, an antiviral drug ribavirin and palivizumab is prescribed along with symptomatic treatment. RSV detection is important to ensure appropriate treatment of children. Most commonly used detection methods for RSV are DFA, ELISA and Real-time PCR which are expensive and time consuming. Newer approach of plasmonic detection techniques like localized surface plasmon resonance (LSPR) spectroscopy using metallic nanomaterials has gained interest recently. The LSPR spectroscopy is simple and easy than the current biophysical detection techniques like surface-enhanced Raman scattering (SERS) and mass-spectroscopy. Results: In this study, we utilized LSPR shifting as an RSV detection method by using an anti-RSV polyclonal antibody conjugated to metallic nanoparticles (Cu, Ag and Au). Nanoparticles were synthesized using alginate as a reducing and stabilizing agent. RSV dose and time dependent LSPR shifting was measured for all three metallic nanoparticles (non-functionalized and functionalized). Specificity of the functionalized nanoparticles for RSV was evaluated in the presence Pseudomonas aeruginosa and adenovirus. We found that functionalized copper nanoparticles were efficient in RSV detection. Functionalized copper and silver nanoparticles were specific for RSV, when tested in the presence of adenovirus and P. aeruginosa, respectively. Limit of detection and limit of quantification values reveal that functionalized copper nanoparticles are superior in comparison with silver and gold nanoparticles. Conclusions: The study demonstrates successful application of LSPR for RSV detection, and it provides an easy and inexpensive alternative method for the potential development of LSPR-based detection devices.